Microstructure and build defects investigation of 3D-printed steel parts - Lai, Jun Han (2019)
To determine the feasibility of DED process for manufacturing API 5L X65 steel for use in pipelines, the microstructure and build defects of DED-printed API 5L X65 steel were observed and analysed. Specimens were cut and mounted from samples that have undergone tensile and fatigue tests in 0° and 45° build orientations, as well as horizontal and vertical cross-sections. They were subsequently observed using OM and SEM to determine porosity, microstructure and the presence of inclusions, and analysed using ImageJ and EDS software. Calculated porosity levels were similar for both horizontal and vertical cross-sections with a mean porosity value of 0.3±0.1%. The thickness of each layer was determined from the analysis of vertical cross-sectional view of the sample, and mean layer thickness was found to be ~570 μm. The dimensions of the melt pool were also determined, and its mean width and depth were ~2533.8 μm and 446.7 μm. The microstructure appears to be predominantly martensitic at the melt pool boundary, while martensite with colonies of pearlite were observed within the melt pool. Few inclusions were observed within the samples, which were mostly non-metallic in nature with sizes below 50 μm.